If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -1 + 10x = 5(2x + 3) + 4 Reorder the terms: -1 + 2x + 10x = 5(2x + 3) + 4 Combine like terms: 2x + 10x = 12x -1 + 12x = 5(2x + 3) + 4 Reorder the terms: -1 + 12x = 5(3 + 2x) + 4 -1 + 12x = (3 * 5 + 2x * 5) + 4 -1 + 12x = (15 + 10x) + 4 Reorder the terms: -1 + 12x = 15 + 4 + 10x Combine like terms: 15 + 4 = 19 -1 + 12x = 19 + 10x Solving -1 + 12x = 19 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. -1 + 12x + -10x = 19 + 10x + -10x Combine like terms: 12x + -10x = 2x -1 + 2x = 19 + 10x + -10x Combine like terms: 10x + -10x = 0 -1 + 2x = 19 + 0 -1 + 2x = 19 Add '1' to each side of the equation. -1 + 1 + 2x = 19 + 1 Combine like terms: -1 + 1 = 0 0 + 2x = 19 + 1 2x = 19 + 1 Combine like terms: 19 + 1 = 20 2x = 20 Divide each side by '2'. x = 10 Simplifying x = 10
| t=-20 | | 5x-4x+9n=2 | | 2(3x-2)=4(x-8) | | 53-w=198 | | 8-8x=68-2x | | 6(x-1)=7x-14 | | y+4(x+5)=40 | | 2m+1=15 | | 36t-8+9t=20 | | 67-7x=29x+21 | | 6x-6x=7x-14 | | 7z-1=3z-29 | | .04c+600=1900 | | 4x^3+2=0 | | 4u-4+28=10u-15 | | 5x-3(5-1x)=1 | | 6x-5=15x-15 | | 128-7x=11x+22 | | -2x+4=17 | | -14r+5=-10r+9 | | 220=132-w | | 7x+3=49 | | x^2+12x-31=3x+5 | | 6(2g-3h)-5g= | | -15=5+5y | | 8x+10=6x+6 | | 13x^2+43x+69=0 | | 1.5y-6=1.25(x+6) | | 24x-16=19x+19 | | -2(6x-7)=-82 | | 8(3x+4)=12x+24 | | 5n-2=2n-5 |